1997
DOI: 10.1016/s0092-8674(00)81904-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Demonstration of a Role for PKA in the Late Phase of LTP and in Hippocampus-Based Long-Term Memory

Abstract: To explore the role of protein kinase A (PKA) in the late phase of long-term potentiation (L-LTP) and memory, we generated transgenic mice that express R(AB), an inhibitory form of the regulatory subunit of PKA, only in the hippocampus and other forebrain regions by using the promoter from the gene encoding Ca2+/ calmodulin protein kinase IIalpha. In these R(AB) transgenic mice, hippocampal PKA activity was reduced, and L-LTP was significantly decreased in area CA1, without affecting basal synaptic transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

58
958
4
7

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,137 publications
(1,035 citation statements)
references
References 38 publications
58
958
4
7
Order By: Relevance
“…AMYGFamygdala; CPuFcaudate putamen; HIPPFhippocampus; IC/SCFinferior/superior colliculus; NAccFnucleus accumbens; PnCFpontine reticular nucleus; PPTNFpedunculopontine tegmental nucleus; SMNFspinal motoneurons; VPFventral pallidum; and VTAFventral tegmental area. Houslay and Adams, 2003;Rochais et al, 2004), we tested the effects of crossing Gas* transgenic mice to another line of transgenic mice expressing the PKA inhibitor R(AB) (Abel et al, 1997). Together, our results show that Gas* expression results in a complex, brainregion-specific biochemical response that ultimately leads to deficits in PPI.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…AMYGFamygdala; CPuFcaudate putamen; HIPPFhippocampus; IC/SCFinferior/superior colliculus; NAccFnucleus accumbens; PnCFpontine reticular nucleus; PPTNFpedunculopontine tegmental nucleus; SMNFspinal motoneurons; VPFventral pallidum; and VTAFventral tegmental area. Houslay and Adams, 2003;Rochais et al, 2004), we tested the effects of crossing Gas* transgenic mice to another line of transgenic mice expressing the PKA inhibitor R(AB) (Abel et al, 1997). Together, our results show that Gas* expression results in a complex, brainregion-specific biochemical response that ultimately leads to deficits in PPI.…”
Section: Introductionmentioning
confidence: 91%
“…This transgene is expressed in addition to the endogenous genomic copy of Gas, which we have verified remains functional (as indicated by increased adenylyl cyclase activity in response to GTPgS stimulation; data not shown). As described previously (Abel et al, 1997), R(AB) mice express a dominant-negative regulatory subunit for PKA, resulting in inhibited PKA activity. Expression of both the Gas* and R(AB) transgenes are driven by the CaMKIIa promoter, which restricts expression to postnatal forebrain neurons (see Figure 1b for expression pattern).…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is usually formed by multiple pairing trials but not by a single trial. It has been demonstrated that the cAMP signaling system plays critical roles in producing LTM, or long-term synaptic plasticity considered to underlie LTM formation, in mammals [1], insects [6,19] and mollusks [2]. In all of these animals, production of cAMP stimulates PKA, and this activates the transcription factor CREB (cAMP element-binding protein).…”
Section: Main Textmentioning
confidence: 99%